Strategi Lanjut Usia Mengurangi Ketidakpastian Komunikasi Dalam Menjalin Hubungan Pertemanan (Studi Kasus di Balai Perlindungan Sosial Tresna Werdha Ciparay) - Septadinusastra, Vina Alvinia (Media Nusantara, 2022)
Every elderly person who comes to the nursing home must adjust so that they can hang out with their friends. However, the elderly often feel afraid to start communication because uncertainty arises in him. In general, this study aims to know the strategy of the elderly to reduce uncertainty in making friendships, to know the efforts of the elderly in adapting in the nursing home environment, and to know the obstacles faced by the elderly in establishing friendship relationships. The method used is qualitative method with case study approach in elderly living in Balai Perilindungan Tresna Werdha. Data collection is done by conducting observations, interviews, and library studies. From the results of the study revealed that the elderly strategy reduces uncertainty in establishing friendship relationships, namely conducting passive strategies where the elderly secretly observe other elderly and active strategies where the elderly observe the target by digging information about the target from other seniors. Furthermore, the efforts of the elderly in adapting in the nursing home environment are done by being friendly and polite, being quiet and indifferent, finding suitable friends, and understanding the character of the elderly. While the obstacles faced by the elderly are language barriers, habitual living constraints, the background of elderly life, and elderly characters. This study concluded that the elderly need a strategy to reduce uncertainty so that they can adjust, have good friends, and survive in the nursing home.